Adaptability and Social Support: Examining Links With Psychological Wellbeing Among UK Students and Non-students - Holliman, Andrew J.; Waldeck, Daniel; Jay, Bethany; Murphy, Summayah; Atkinson, Emily; Collie, Rebecca J.; Martin, Andrew (Frontiers in Psychology, 2021)
The purpose of this multi-study article was to investigate the roles of adaptability and social support in predicting a variety of psychological outcomes. Data were collected from Year 12 college students (N = 73; Study 1), university students (N = 102; Study 2), and non-studying members of the general public (N = 141; Study 3). Findings showed that, beyond variance attributable to social support, adaptability made a significant independent contribution to psychological wellbeing (life satisfaction, psychological wellbeing, flourishing, and general affect) and psychological distress across all studies. Beyond the effects of adaptability, social support was found to make a significant independent contribution to most wellbeing outcomes (but not psychological distress in university students). In a multi-group analysis comparing predictors of psychological wellbeing in university students and non-studying adults, where the same outcome measures were used (Study 4; N = 243), it was found that adaptability played a stronger role (relative to social support) for university students, whereas social support played a stronger role for non-studying adults. Finally, (contrary to expectations) there was no evidence of an interaction between adaptability and social support predicting psychological outcomes—adaptability and social support operated as independent main effects. These findings demonstrate the importance of adaptability and social support in uniquely predicting psychological wellbeing in different sample groups. It is argued here that these two factors, should be given greater consideration in discussions of psychological wellbeing, and are relevant to psychological wellbeing at different major developmental life stages.